Pharmacokinetics and pharmacodynamics of levofloxacin injection in healthy Chinese volunteers and dosing regimen optimization. (24th May 2013) - Cao, G.; Zhang, J.; Wu, X.; Yu, J.; Chen, Y.; Ye, X.; Zhu, D.; Zhang, Y.; Guo, B.; Shi, Y.
Summary: What is known and objective: The pharmacokinetics (PK) and pharmacodynamics (PD) of levofloxacin were investigated following administration of levofloxacin injection in healthy Chinese volunteers for optimizing dosing regimen. Methods: The PK study included single‐dose (750 mg/150 mL) and multiple‐dose (750 mg/150 mL once daily for 7 days) phases. The concentration of levofloxacin in blood and urine was determined using HPLC method. Both non‐compartmental and compartmental analyses were performed to estimate PK parameters. Taking f Cmax /MIC ≥5 and f AUC24 h /MIC ≥30 as a target, the cumulative fraction of response (CFR) of levofloxacin 750 mg for treatment of community‐acquired pneumonia (CAP) was calculated using Monte Carlo simulation. The probability of target attainment (PTA) of levofloxacin at various minimal inhibitory concentrations (MICs) was also evaluated. Results and discussion: The results of PK study showed that the Cmax and AUC0–∞ of levofloxacin were 14·94 μg/mL and 80·14 μg h/mL following single‐dose infusion of levofloxacin. The half‐life and average cumulative urine excretion ratio within 72 h post‐dosing were 7·75 h and 86·95%, respectively. The mean Css, max, Css, min and AUC0–τ of levofloxacin at steady state following multiple doses were 13·31 μg/mL, 0·031 μg/mL and 103·7 μg h/mL, respectively. The accumulation coefficient was 1·22. PK/PD analysis revealed that the CFR value of levofloxacin 750‐mg regimen against Streptococcus pneumoniae was 96·2% and 95·4%, respectively, in terms of f Cmax /MIC and f AUC/MIC targets. What is new and conclusion: The regimen of 750‐mg levofloxacin once daily provides a satisfactory PK/PD profile against the main pathogenic bacteria of CAP, which implies promising clinical and bacteriological efficacy for patients with CAP. A large‐scale clinical study is warranted to confirm these results.